Magnetic Field Models and their Application in Optimal Magnetic Divertor Design. Issue 6 (12th July 2016) - Blommaert, M.; Baelmans, M.; Heumann, H.; Marandet, Y.; Bufferand, H.; Gauger, N. R.; Reiter, D.
Abstract: In recent automated design studies, optimal design methods were introduced to successfully reduce the often excessive heat loads that threaten the divertor target surface. To this end, divertor coils were controlled to improve the magnetic configuration. The divertor performance was then evaluated using a plasma edge transport code and a "vacuum approach" for magnetic field perturbations. Recent integration of a free boundary equilibrium (FBE) solver allows to assess the validity of the vacuum approach. It is found that the absence of plasma response currents significantly limits the accuracy of the vacuum approach. Therefore, the optimal magnetic divertor design procedure is extended to incorporate full FBE solutions. The novel procedure is applied to obtain first results for the new WEST (Tungsten Environment in Steady‐state Tokamak) divertor currently under construction in the Tore Supra tokamak at CEA (Commissariat à l'Energie Atomique, France). The sensitivities and the related divertor optimization paths are strongly affected by the extension of the magnetic model. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)